VERB MOOD - Xabibullayeva , Madinaxon Xurshid qizi (Educational Research in Universal Sciences, 2024)
The aim of this course is to provide the readers about the category of mood of the verb. The main aim of the category of mood of the verb is indicates the speaker’s attitude to the action expressed by the verb. The mode of the verb determines whether the speaker considers the action real, desirable, doubts its possibility, or considers it conditional or unrealistic.